La corrupción en España: rasgos y causas esenciales - Manuel Villoria (Cahiers de Civilisation Espagnole Contemporaine)
This article tries to show the main characteristics of one of the most important problems that suffers Spain: corruption. According to our research, Spain does not suffer a problem of systemic corruption, but it has a lot of political corruption. This kind of corruption is frequently highlighted by the media and linked to the economic problems of the country, mainly unemployment, creating a big problem of disaffection and distrust in our political institutions.